U.S. tanker transport: Current structure and economic analysis. (December 2017) - Duru, Okan; Clott, Christopher; Mileski, Joan P.
Abstract: With the advent of hydraulic fracturing, e.g. "fracking" in North America and United States policy changes on the export of crude oil and natural gas, it is anticipated that major structural changes will occur in the maritime transport of these commodities. The impact of these changes are global; however, regional transportation in North America is also expected to have profound impacts. This paper investigates these structural changes and the potential impact in the short-term and long-term effects on tanker shipping with data from tanker traffic in the major U.S. liquid bulk ports as well as crude oil and oil product movements recorded by the U.S. Energy Information Administration. We find a significant increase in U.S. oil and oil based product exports and a corresponding decline in imports in the recent years and the near future. The domestic market shows an increase in tanker traffic from the Gulf Coast to the East Coast of the U.S. Based on these current developments, four potential scenarios emphasize the growth or decline of tanker shipping (also tanker freight rates) connected to the U.S. waterborne wet bulk trades. Both public and private decision makers need to make delicate investment choices strongly tied to oil price variations. Considering the prospects on rising oil prices in the long-run, a significant downgrade of crude oil shipping and uprising oil product shipping are some fundamental results to be considered by key decision making units in the industry.